Stability Analysis and Combination-Combination Synchronization of the Chaotic System - Shukla, Vijay K.; Joshi, Mahesh C. (Journal of Applied Nonlinear Dynamics, 2026)
This work examines the analysis of Jacobi stability of the Sprott-C system by using the KCC-theory. The five KCC invariants are obtained to study the system's characteristics. We also calculate the spherical and ellipsoidal ultimate bound of the ecological model. Further, we analyze combination-combination synchronization among chaotic systems with delay and without delay terms. To see the effect of time-delay on combination-combination synchronization we are considering the time-delay ecological chaotic system. By designing suitable controllers, the synchronization among these systems is achieved. Finally, numerical results validate the feasibility of the designed control method.